Humanitarian diplomacy in the Asia-Pacific : part II - Cook, Alistair David Blair (2022)
This special issue is the second of a two-part series guest edited by Alistair D. B. Cook and Lina Gong that examine how countries and regional organisation in Asia and the Pacific understand and conduct humanitarian diplomacy. The current issue consists of perspectives from Japan, Indonesia and the Philippines. Gomez explains why Japan has been at the periphery of the international humanitarian system. He advances two explanations for Japan’s peripheral standing, which include the difficulty for Japan to adapt to the humanitarian institutions that are dominated by western norms and values, and Japan’s strength and preference for an integrated approach to humanitarian crises through multiple international cooperation means. Marzuki and Tiola discuss Indonesia’s perspectives and scope of humanitarian engagement which include providing emergency relief in conflict and non-conflict settings as well as participating in UN peacekeeping operations. They argue that Indonesia’s own struggle with disasters and its identity as a member of ASEAN and a Muslim-majority country are key factors shaping its conduct of humanitarian diplomacy.